Novel Sgmentation Technique for Synthetic Aperture Radar Target Tracking using Hybrid PSO Method - Malakonda Reddy, B; Zia Ur Rahman, Md (International Journal of Engineering and Technology, 2018)
In remote sensing applications, it is evidently electromagnetic imaging has more advantages than optical imaging due to its horizon. In such a contest synthetic aperture radars (SAR) plays a vital role. In SAR image processing, segmentation is a key step in identifying and tracking targets, terrain features.Â Hence, this paper, we present an Improved hybrid PSO method proposed based on multilevel threshold for enhancing the image for segmentation. Experimental results indicate, the proposed methods enhance the edge features effectively with compare to Otsu, Modified Otsu and Region Based Active contour methods.Â